The Planar Lateral Wave Antenna - Tokan, Fikret; Tokan, Nurhan Turker; Neto, Andrea (IEEE, 2012)
A novel planar lateral wave antenna concept that promises impedance matching over factor a one to three bandwidth, very high efficiency, and high directivity in one plane in presented. The structure realizes a planar elliptical dielectric lens antenna for focusing the beams in the H-plane. A broad band feed launches wave within a parallel plate waveguide region, filled with dense dielectric. These waves realize a directive and almost frequency independent aperture field configuration, exploiting a novel lateral wave propagation mechanism.
Keywords: Engineering; Telecommunications